Assessing the drivers of wetland changes in areas associated with wildlife-based tourism activities in Zimbabwe - Marambanyika, Thomas (IntechOpen, 2019)
The study assesses wetland land cover changes associated with high wildlife densities and tourism activities in Dete vlei, located in Sikumi protected forest, adjacent to Hwange National Park, Zimbabwe. The vlei is used for photographic safaris and is associated with high number of tourists visiting the wetland to see a variety of wildlife species congregated in it. On-screen digitization and analysis of SPOT images for the period of 1984–2013 was used to determine land cover changes in the wetland. Field data were collected through observations, measurements and semi-structured interviews with key informants. The results of the study showed that the spatial extent of bare areas increased in the lower section of the vlei after the establishment of salt licks and watering points meant to attract many wild animals during the dry season. In contrast, wetland conditions have been expanding in the upper section of the wetland without artificial salt licks and watering points. Tourists’ footpaths, road culverts, unplanned vehicles’ roads, to mention a few, contribute to erosional features evident in the wetland. The study recommends the introduction of wildlife-based tourism management strategies in seasonal wetlands to minimise degradation and possibly loss of wetlands.